2022
DOI: 10.1039/d2mo00088a
|View full text |Cite
|
Sign up to set email alerts
|

Food authentication: truffle species classification by non-targeted lipidomics analyses using mass spectrometry assisted by ion mobility separation

Abstract: Truffles are appreciated as food all over the world because of their extraordinary aroma. However, quantities are limited and successful cultivation in plantations is very labor-intensive and expensive, or even...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…In food research, untargeted methods can be useful to discover the lipidome of a given food. Untargeted lipidomics can, for example, be used to classify different truffle species (Creydt & Fischer, 2022), to differentiate bovine milk from different feeding regimes (Wölk et al., 2022), and to follow changes of lipid profiles in different types of meat induced by irradiation (Chiesa et al., 2022). The combination of untargeted and targeted lipidomics in so‐called pseudo‐targeted manner, combining the high lipidome coverage from untargeted approaches with the high sensitivity and reliability of targeted methods (Xu, Hu, et al., 2020), will be helpful in the elucidation of food lipidomes.…”
Section: Analytical Challenges In Food Lipidomicsmentioning
confidence: 99%
“…In food research, untargeted methods can be useful to discover the lipidome of a given food. Untargeted lipidomics can, for example, be used to classify different truffle species (Creydt & Fischer, 2022), to differentiate bovine milk from different feeding regimes (Wölk et al., 2022), and to follow changes of lipid profiles in different types of meat induced by irradiation (Chiesa et al., 2022). The combination of untargeted and targeted lipidomics in so‐called pseudo‐targeted manner, combining the high lipidome coverage from untargeted approaches with the high sensitivity and reliability of targeted methods (Xu, Hu, et al., 2020), will be helpful in the elucidation of food lipidomes.…”
Section: Analytical Challenges In Food Lipidomicsmentioning
confidence: 99%
“…In order to reduce these effects, multiplexing strategies are used, in which further ion packets are guided into the drift zone, even if the previous ion packet has not yet completely crossed the drift zone. Using Hadamard transformation, the data can then be separated again (Figure 3) [12,110,[115][116][117].…”
Section: Ion Mobility Spectrometrymentioning
confidence: 99%
“…A large part of the published study is more target-based and focuses on certain analyte groups, such as mycotoxins [139], pesticides [140], and veterinary drugs [141]. Nontargeted studies were conducted during the roasting process of coffee [142], characterization of wine [143] and ginseng [144], and species/varietal differentiation of truffles [12] and potatoes [11].…”
Section: Ion Mobility Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Mannina et al have shown on Tuber aestivum that 1 H NMR of aqueous truffle extracts can be used to study their chemical composition ( Tuber aestivum , named by Carlo Vittadini, , and Tuber uncinatum were summarized as Tuber aestivum , on the basis of molecular biological findings that Tuber aestivum and Tuber uncinatum are the same species). Although Creydt et al and Losso et al have recently shown that liquid chromatography electrospray ionization ion mobility quadrupole time-of-flight mass spectrometry (LC-ESI-IM-QTOF-MS) respectively direct analysis in real time mass spectrometry (DART-MS) and hydrophilic interaction liquid chromatography mass spectrometry (HILIC-ESI-MS) can make very good predictions in the classification of truffle species; it is reasonable to use NMR as an alternative analytical method, thanks to the particular advantages that this method offers.…”
Section: Introductionmentioning
confidence: 99%